Ответы и объяснения

  • lm6
  • середнячок
2013-01-07T09:47:03+00:00

cos2x+cos6x=0

cosx+cosy=2cos((x+y)/2)*cos((x-y)/2)

сумму косинусов заменяем и получаем сдедующее

2cos((2x+6x)/2)*cos((2x-6x)/2)=0

cos4x=0                                  cos(-2x)=0

4x=+-arccos(0)+2πn            2x=+-arccos(0)+2πn

x=(+-π/2+2πn)/4                    x=(+-π/2+2πn)/2

 

 

  • Участник Знаний
2013-01-07T09:47:10+00:00

cos2x+cos6x=0

2cos4xcos(-2x)=0

cos4x=0

x=-π/8+πn/4, n∈Z

cos(2x)=0

x=-π/4+πn/2, n∈Z